CD36 promotes de novo lipogenesis in hepatocytes through INSIG2-dependent SREBP1 processing - Han Zeng; Hong Qin; Meng Liao; Enze Zheng; Xiaoqing Luo; Anhua Xiao; Yiyu Li; Lin Chen; Li Wei; Lei Zhao; Xiong Z. Ruan; Ping Yang; et al. (Elsevier, 2022)
Objective: Enhanced de novo lipogenesis (DNL) in hepatocytes is a major contributor to nonalcoholic fatty liver disease (NAFLD). Fatty acid translocase (FAT/CD36) is involved in the pathogenesis of NAFLD through facilitating free fatty acids uptake. Here, we explored the effects of CD36 on DNL and elucidated the underlying mechanisms. Methods: We generated hepatocyte-specific CD36 knockout (CD36LKO) mice to study in vivo effects of CD36 on DNL under high-fat diet (HFD). Lipid deposition and DNL were analyzed in primary hepatocytes isolated from CD36LKO mice or HepG2 cells with CD36 overexpression. RNA sequence, co-immunoprecipitation, and proximity ligation assay were carried out to determine its role in regulating DNL. Results: Hepatic CD36 expression was upregulated in NAFLD mice and patients, and CD36LKO mice exhibited attenuated HFD-induced hepatic steatosis and insulin resistance. We identified hepatocyte CD36 as a key regulator for DNL in the liver. Sterol regulatory element-binding protein 1 (SREBP1) and its downstream lipogenic enzymes such as FASN, ACCα, and ACLY were significantly downregulated in the liver of HFD-fed CD36LKO mice, whereas overexpression CD36 stimulated insulin-mediated DNL and lipid droplet formation in vitro. Mechanistically, CD36 was activated by insulin and formed a complex with insulin-induced gene-2 (INSIG2) that disrupts the interaction between SREBP cleavage-activating protein (SCAP) and INSIG2, thereby leading to the translocation of SREBP1 from ER to Golgi for processing. Furthermore, treatment with 25-hydroxycholesterol or betulin molecules shown to enhance SCAP-INSIG interaction, reversed the effects of CD36 on SREBP1 cleavage. Conclusions: Our findings identify a previously unsuspected role of CD36 in the regulation of hepatic lipogenic program through mediating SREBP1 processing by INSIG2, providing additional evidence for targeting CD36 in NAFLD.